Developing the Quality of Work Life in Light of the Relationship Between Organizational Ignorance and Job Conflict: an Exploratory Study of the Opinions of a Sample of Nurses in the Medical City Hospital - Abdel Salam Abdel-Daem, Ali (Journal of Economics and Administrative Sciences, 2024)
Purpose: Developing the quality of work life as a logical indicator for studying the relationship between practical organizational ignorance and its influential role in determining organizational conflict for nurses at Medical City Hospital. Theoretical framework: The study shed light on enhancing the organization’s organizational ignorance according to the available data and information, and to the researcher’s knowledge, other researchers have yet to address it. Design/methodology/approach: The exploratory approach was adopted in presenting and measuring the concepts of organizational ignorance and functional conflict based on the questionnaire because it was applied in its quantitative form through standard models and applied at the level of the Medical City Hospital in Baghdad. A research population of the Medical City Complex was taken, and a sample of nurses was selected to become (85) individuals, excluding two individuals due to the lack of a complete answer, so that the sample for analysis became (83) nurses only. Findings: Organizational ignorance has a distinct role in determining organizational conflict in overt, perceived, and implicit conflict related to implementing the strategy and developing the quality of work life in the Medical City. Research, Practical & Social implications: An intellectual presentation perspective on organizational ignorance and its few dimensions in job conflict using thoughtful methods. Originality/value: The research topic was applied to the Medical City Hospital in Baghdad, which is considered an essential institution in Iraq due to its unique organization and orientation, increasing the study’s credibility and importance to society.